Adherence to a vegetable dietary pattern attenuates the risk of non‐alcoholic fatty liver disease in incident type 2 diabetes: The TCLSIH cohort study. (22nd December 2021) - Xia, Yang; Cao, Limin; Zhang, Qing; Liu, Li; Zhang, Shunming; Meng, Ge; Wu, Hongmei; Gu, Yeqing; Sun, Shaomei; Wang, Xing; Zhou, Ming; Jia, Qiyu; et al.
Abstract: Background: Non‐alcoholic fatty liver disease (NAFLD) is a strong risk factor for type 2 diabetes. However, no study has investigated whether dietary intake can modify this effect. Therefore, we aimed to investigate the effect of dietary pattern modification on the association between NAFLD and type 2 diabetes. Methods: A large prospective cohort study ( n = 24, 602) was conducted in China. NAFLD was diagnosed using liver ultrasonography considering alcohol consumption. Dietary data were assessed using a validated self‐administered food frequency questionnaire. Cox proportional hazards regression was used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Results: Following a 93, 873 person‐year follow‐up, 787 (3.20%) participants developed type 2 diabetes. In a multivariable adjusted model, compared with participants without NAFLD, the HR (95% CI) of incident type 2 diabetes for NAFLD patients was 3.04 (2.51, 3.68). On subgroup analyses, the adjusted HRs (95% CIs) of incident type 2 diabetes for NAFLD patients with low (≤median score) and high (>median score) vegetable pattern intakes were 4.08 (3.05, 5.46) and 2.38 (1.85, 3.07) ( p for interaction <0.01), respectively. Higher vegetable intake was also found to attenuate the risk effect of phenotype groups of NAFLD on incident type 2 diabetes, especially in the lean NAFLD group. Conclusions: The present study demonstrated that NAFLD is a strong risk factor for type 2 diabetes in the Chinese population. Notably, adherence to a dietary pattern rich in vegetables can attenuate this risk, especially in lean NAFLD patients. Abstract :